The Effect of Sliding Knots on the Suture-Tendon Interface Strength: A Biomechanical Analysis Comparing Sliding and Static Arthroscopic Knots. (February 2013) - Savage, Albert J.; Spruiell, Murray D.; Schwertz, Joseph M.; McGwin, Gerald; Eberhardt, Alan; Ponce, Brent A.
Background: The tissue-suture interface remains the most common site of failure in rotator cuff repairs. It is currently unknown if arthroscopic sliding knots injure the tissue and weaken the suture-tendon interface. Purpose: To evaluate the effect sliding knots have on the strength of the suture-tendon interface. Study Design: Controlled laboratory study. Methods: A total of 32 sheep infraspinatus tendons were randomized among 4 groups of stitches (n = 8): simple-static, simple-sliding, mattress-static, and mattress-sliding. All high-strength, No. 2 suture stitch-knot combinations were created in an arthroscopic simulated environment, and sliding knots were tied with shortening of the suture and sliding of the knot down to the tissue interface to simulate surgical technique. Each graft was cyclically loaded on a mechanical testing system from 5 to 20 N for 20 cycles and then loaded to failure. A least squares analysis of variance model was used to test significance of sliding stitches upon cyclic elongation, peak-to-peak displacement, and ultimate load. Estimated means and standard deviations are reported from the regression model. Results: A mattress-static stitch (116 N) was significantly stronger than a mattress-sliding stitch (70 N; P < .001). The ultimate loads for the simple-static (46 N) and sliding (50 N) stitches were not statistically different. For cyclic elongation, the only difference was the mattress-sliding stitch (0.95 mm) having a greater elongation than the simple-static (0.61 mm; P = .01) and simple-sliding (0.68 mm; P = .04) stitches. Both mattress stitches had significantly less peak-to-peak displacement (0.39 and 0.41 mm) than the simple stitches (0.47 and 0.46 mm; P < .001). Conclusion: Sliding suture through tissue weakens the suture-tendon interface in mattress stitch constructs but not in simple stitch constructs. Mattress stitches have superior holding strength compared with simple stitches. Clinical Relevance: Clinical relevance is uncertain. In situations with poor tissue quality or concern regarding tension across the repair, consideration should be given to using static knots as opposed to sliding knots when placing mattress stitches.